Artificial Intelligence’s Role in Enhancing MSMEs Revenue through Digital Promotion - Sahat Renol HS; Selvita Eka Eviana Purba; Sjeddie R Watung; Ramon Arthur Ferry Tumiwa; Jessylistina Hercyliana Langi (Universitas Negeri Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the global economy but face challenges in effectively leveraging artificial intelligence (AI)-based digital marketing. This study aims to analyze the effects of automation, personalization (PER), and advertising efficiency (EFF) on marketing performance (MP) and their implications for MSME revenue (REV). Data were collected through a cross-sectional survey of 95 MSMEs in North Sumatra that have adopted AI-based digital promotions. The questionnaire consisted of 25 indicators covering five constructs: AUT (5 items), PER (5 items), EFF (5 items), MP (5 items), and REV (5 items). The analysis was conducted using SEM-PLS. The results indicate that AUT (p = 0.000), PER (p = 0.011), and EFF (p = 0.000) significantly influence MP but do not have a direct effect on REV (p > 0.05). In contrast, MP (p = 0.000) serves as a key mediator, channeling the benefits of AI-based strategies into revenue growth. The research model explains 51% of the variance in Marketing Performance and 29.8% of the variance in Revenue. These findings underscore that the impact of AI on MSME revenue is indirect, occurring through enhanced marketing effectiveness, customer engagement, and promotional innovation. The implications suggest that strengthening digital capabilities, visionary leadership, and adequate technological infrastructure are prerequisites for MSMEs to fully exploit AI potential. Therefore, an integrated AI-based marketing strategy can enhance both competitiveness and financial performance of MSMEs in the digital era.